Penguatan Kapasitas Dokter dalam Diagnosis Cedera Penyelaman dan Envenomasi dengan Pendekatan Bahasa Lokal Sasak - Yoga Pamungkas Susani; Wahyu Sulistya Affarah; Eustachius Hagni Wardoyo; Putu Suwita Sari; Basuki Rahmat; Ima Arum Lestarini; Alfian Muhajir; Ni Putu Sasmita Lestari; Nurman Saputra (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Coastal primary care physicians in West Nusa Tenggara (NTB) serve as the frontline responders for diving injuries and marine envenomation, yet their diagnostic capacity for these cases remains limited despite the high likelihood of such incidents in coastal communities. To address this gap, this community engagement activity primarily aimed to enhance physicians’ diagnostic abilities, with the incorporation of Sasak local-language symptom descriptors used as a supporting tool to improve clinical anamnesis and patient communication. An online webinar was conducted involving 114 internship doctors, assessed through a pre-test, post-test, and a Likert-scale evaluation questionnaire. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank test. Most participants were from Mataram City (41.23%) and graduates of NTB universities (59.6%). Participants perceived the inclusion of Sasak language terms as highly relevant for improving clinical interactions (mode = 5). The mean test score increased from 133.9 (pre-test) to 165.4 (post-test), with a significant improvement demonstrated by the Wilcoxon test (Z = –4.944; p < 0.001). These findings indicate that the webinar effectively strengthened physicians’ diagnostic capacity for diving injuries and marine envenomation, with local-language familiarity functioning as an additional supportive competency. Further development into a structured anamnesis module incorporating these elements is recommended.